1997
DOI: 10.1038/sj.onc.1201496
|View full text |Cite
|
Sign up to set email alerts
|

Activation of c-Src by receptor tyrosine kinases in human colon cancer cells with high metastatic potential

Abstract: Recent data suggest that signal transduction may have a critical role in the development and regulation of the metastatic phenotype. Here, we investigated the role of c-Src activation in the process of human colon cancer metastasis to the liver. Our data, derived from two di erent sets of human colon cancer cell line metastatic variants, suggest that not only do highly-metastatic cells display constitutively elevated c-Src protein kinase activity when compared to poorly metastatic cells, but also that receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
118
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(124 citation statements)
references
References 24 publications
6
118
0
Order By: Relevance
“…A number of human primary tumours and tumour-derived cell lines including leukaemias possess elevated Src kinase activities (Rosen et al, 1986;Ottenhoff-Kalff et al, 1992;Talamonti et al, 1993;Mao et al, 1997;Donato et al, 2003). For instance, Lyn and Hck have been implicated in the oncogenic activity of Bcr-Abl in haematopoietic cells (Danhauser-Riedl et al, 1996;Hu, Nature genetics, 2004) and with the use of dominant-negative src mutants or pharmacological inhibitors have confirmed that these two kinases contribute to the Bcr-Abl-induced Tel-Abl induces oncogenic signalling via Hck C Pecquet et al Bcr-Abl-transformed haematopoietic cells.…”
Section: Discussionmentioning
confidence: 99%
“…A number of human primary tumours and tumour-derived cell lines including leukaemias possess elevated Src kinase activities (Rosen et al, 1986;Ottenhoff-Kalff et al, 1992;Talamonti et al, 1993;Mao et al, 1997;Donato et al, 2003). For instance, Lyn and Hck have been implicated in the oncogenic activity of Bcr-Abl in haematopoietic cells (Danhauser-Riedl et al, 1996;Hu, Nature genetics, 2004) and with the use of dominant-negative src mutants or pharmacological inhibitors have confirmed that these two kinases contribute to the Bcr-Abl-induced Tel-Abl induces oncogenic signalling via Hck C Pecquet et al Bcr-Abl-transformed haematopoietic cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, several candidates have been suggested to disrupt the SH2-pTyr529 intramolecular interaction. These include growth factor receptors, through their association with SFK-SH2 (Mao et al, 1997), and tyrosine phosphatases that dephosphorylate pTyr529 (Liang et al, 2007;Zhu et al, 2007;Zheng et al, 2008). Although probably activated in a subset of tumours, they may not account for the kinase deregulation observed in CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, inhibitors of Src have a key role in cancer treatment (Summy et al, 2005) and Src family kinases can become important targets for anti-cancer therapy in the future (Summy & Gallick, 2003). In addition, c-Src is over-expressed in a HT29 cell line of colon cancer and plays an important role in the development of metastatic stage of primary human colorectal cancer Termuhlen et al, 1993;Mao et al, 1997). Previous study has shown that c-Src antisense oligonucleotides can silent the c-Src expression in the cancer cells (Charles et al, 1997;Irby & Yeatman, 2000).…”
Section: Introductionmentioning
confidence: 99%